The inheritance - Andrews, Ilona (Breach Wars, 2025)
"We are at war. The interdimensional invasion brought us unimaginable suffering, but it also awoke talents slumbering deep within us,a means to repel and destroy our enemy. Every day new gates open, leading to breaches filled with monsters and valuable resources. If you are a Talent, your country needs you. The world needs you. Be thehero you were born to be. Adaline is a Talent. Ten years ago, she had a happy marriage and a job she loved. The invasion shattered both. Now she works for the government, searching the breaches for magicmetals and medicine to help Earth repel an interdimensional enemy. Two kids, one cat, bills, benefits, mortgage and school tuition...Risking her life became routine. She had gone into the dimensional gates hundreds of times. She was always well protected. This time everything goes wrong. Now Ada is trapped in the labyrinth of alien caves unlike any other. Her only companion is a scared German Shepherd named Bear. Together they must uncover the breach's secrets and escape, because Ada promised her children that she will come home. The future of humanity depends on it."--